2021
DOI: 10.1136/bmjopen-2021-051237
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for severe outcomes in people with diabetes hospitalised for COVID-19: a cross-sectional database study

Abstract: AimThis study’s objective was to assess the risk of severe in-hospital complications of patients admitted for COVID-19 and diabetes mellitus (DM).DesignThis was a cross-sectional study.SettingsWe used pseudonymised medical record data provided by six general hospitals from the HM Hospitales group in Spain.Outcome measuresMultiple logistic regression analyses were used to identify variables associated with mortality and the composite of mortality or invasive mechanical ventilation (IMV) in the overall populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 40 publications
(40 reference statements)
4
12
1
Order By: Relevance
“…COVID-19 infection is associated with poorer outcome for those with long-term conditions, such as diabetes, and several potential mechanisms have been proposed [ 6 , 9 ]. This paper specifically examined medications used by many people with diabetes (type 1 and 2) for the prevention of diabetic complications and, therefore, the potential detrimental or beneficial effect of these medications on outcomes for this specific population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…COVID-19 infection is associated with poorer outcome for those with long-term conditions, such as diabetes, and several potential mechanisms have been proposed [ 6 , 9 ]. This paper specifically examined medications used by many people with diabetes (type 1 and 2) for the prevention of diabetic complications and, therefore, the potential detrimental or beneficial effect of these medications on outcomes for this specific population.…”
Section: Discussionmentioning
confidence: 99%
“…Adults with hyperglycaemia at admission, but not pre-existing or subsequent diagnosis of diabetes (based on WHO criteria) were excluded from analysis [ 8 ]. Further descriptions of each nation's dataset have been published previously [ [9] , [10] , [11] , [12] ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic diseases such as DM are associated with an increased risk of a severe COVID-19 illness and death because of their associated hypercoagulation state and uncontrolled inflammation [ 148 ], although it seems that T1DM patients have higher risk than T2DM patients. Epidemiological studies have shown that hospitalization with diabetes and SARS-CoV-2 infection represents as a comorbidity with poor outcome during hospital stay [ 149 ]. A recent study reported that 15% of T2DM patients died from COVID-19, with the poor prognoses for those of elder age and elevated glucose and serum amyloid A levels [ 150 ].…”
Section: Prognosis Of T2dm Patients With Covid-19mentioning
confidence: 99%
“…High glucose level is the basal laboratory test widely used for indicating the risk of poor outcomes (Ortega et al 2021). Impaired Fasting Glucose and diabetes at admission were associated with higher risks of adverse effects among patients with COVID-19 (Zhang et al, 2020).…”
Section: Preexisting Pathology and Covid-19mentioning
confidence: 99%